Energy in international trade law : concepts, regulation and changing markets - Marhold, Anna-Alexandra, 1983- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
Against the backdrop of energy markets that have radically changed in recent decades, this book offers an in-depth study of energy regulation in international trade law. The author seeks to clarify what we define as 'energy' in the context of the applicable international trade rules, and gives the reader a thorough analysis of the concepts, history and law of the various legal frameworks underpinning international energy trade. In addition, several case studies address the ongoing quest for energy security and show how the existing rules relate to some of the vast challenges that energy markets face today, notably the decentralisation and decarbonisation of energy markets.
Energy in the context of international trade law : concepts and changing markets -- The role of energy in international trade law history -- The current WTO legal framework relevant for energy -- Beyond the WTO : the energy charter treaty and preferential trade agreements -- Decentralising energy markets in light of international trade law : OPEC and the EU internal energy market -- Decarbonising energy markets : options for constraining dual pricing and fossil fuel subsidy reform in the WTO -- The emerging concept of 'energy security' in international trade law -- General conclusion and recommendations.
Title from publisher's bibliographic system (viewed on 24 Jun 2021).
Keywords: Power resources -- Law and legislation; Foreign trade regulation